Challenges Concerning the Development of Sustainable Mobility in Cities and Agglomerations - Krawiec, Stanisław (Regional Barometer. Analyses & Prognoses, 2017)
The article presents new challenges facing the municipal, metropolitan and regional governments, associated with the process of technology development and deployment of sustainable transport. Particular attention was paid to the creation of new transport systems based on the electromobility technologies. The aim of the article is to present the changes in the mobility culture as a result of transport technology development and taking into account the needs of environmental protection. Particular attention was paid to the e-mobility development which is a form of mobility that is based on electric drive and respect for ecological conditions.